2014
DOI: 10.1186/1471-2164-15-146
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel and conserved miRNAs involved in pollen development in Brassica campestris ssp. chinensi s by high-throughput sequencing and degradome analysis

Abstract: BackgroundmicroRNAs (miRNAs) are endogenous, noncoding, small RNAs that have essential regulatory functions in plant growth, development, and stress response processes. However, limited information is available about their functions in sexual reproduction of flowering plants. Pollen development is an important process in the life cycle of a flowering plant and is a major factor that affects the yield and quality of crop seeds.ResultsThis study aims to identify miRNAs involved in pollen development. Two indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 56 publications
(69 reference statements)
6
70
0
Order By: Relevance
“…Brassica rapa) [95], suggesting their possible roles in pollen wall development. Notably, silencing of BcMF11, a non-coding RNA gene in Chinese cabbage (Brassica campestris), leads to aborted pollen [96].…”
Section: Epigenetic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Brassica rapa) [95], suggesting their possible roles in pollen wall development. Notably, silencing of BcMF11, a non-coding RNA gene in Chinese cabbage (Brassica campestris), leads to aborted pollen [96].…”
Section: Epigenetic Controlmentioning
confidence: 99%
“…Recent cryo-fixation studies from rice, maize [69], and Arabidopsis [12] have already demonstrated the power of cryo-fixation in obtaining novel ultrastructural features, mainly owing to improved sample preservation. Moreover, previous omics studies indicate the appearance of stage-specific or tissue-specific proteins [11], genes [95], and metabolites [43,56] during pollen wall development, highlighting the importance of systems biology in research on pollen wall development. Together with in vivo imaging, scanning, and cell-specific expression systems, omics studies may help us to fully understand the dynamic molecular and ultrastructural nature of pollen wall development.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Most novel miRNAs detected in other plants or in the diverse biological processes of different plants also showed low expression abundance. Furthermore, these novel miRNAs are usually specific to a species or developmental phase (Wei et al, 2011; Peng et al, 2012; Jiang et al, 2014; Li et al, 2015; Qu et al, 2016). These results indicated that the predicted novel miRNAs were evolutionarily young with important roles in maintaining species-specificity regardless of their expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several similar results have been reported in Brassica campestris ssp. Chinensis [24,25], radish [26] and soybean [27]. …”
Section: Introductionmentioning
confidence: 99%